Revised description of a poorly known Mediterranean Dictyoceratid bath sponge, Spongia (Spongia) zimocca (Schmidt, 1862) (Porifera: Demospongiae: Dictyoceratida) - Castritsi-Catharios, Jeanne; van Soest, Rob W. M.; Kefalas, Efthimios; Vacelet, Jean (Zootaxa, 2011)
Spongia (Spongia) zimocca (Schmidt, 1862) is a real problem for taxonomists. This is due to the fact that it exhibits a wide diversity of forms as well as similarities with other species of the genus. Nevertheless, professional sponge fishermen are able to recognize this species easily based on their own empirical criteria. The lack of easily recognized taxonomic characters in conjunction with the ambiguity concerning the original description makes necessary an updated description of the species. We tried to solve the uncertainty existing among the taxonomists who have been involved with the description of this Mediterranean sponge, basing our description on the Schmidt type specimen and on material deposited in the Amsterdam Museum. In this paper we have summoned up not only the known morphological characters used for the identification of other species belonging to this genus (color, size, shape, skeleton structure, size of the fibers) but also additional morphological characters, used for a first time, aiming to obtain a clearer picture. These new characteristics are: tensile strength, skeletal density, morphology of the conules and the organic content of the fiber mass.